The Sculling Crime in Work Relationship over Plantation Service, Sago Drugging Case Study - Nelly Dharma; Markoni Markoni; Wasis Susetio (Penerbit Kemala Indonesia, 2021)
The judicial process will be ends with a final decision (verdict). Here, the imposition or release of criminal sanctions (punishment), in the judgment has been considered over verdict. Before arriving at this stage, there are steps that must be carried out beforehand, namely the stage of proof in imposing a crime against the defendant. In imposing a crime, the judge must have analyse based on two valid evidence with the two pieces of evidence also judge is convinced that the criminal act charged has actually occurred and it was the defendant who committed it. This is regulated in Article 183 KUHAP. Thus, the purpose of this study to examine and analyse the authority of the prosecutor over judges panel in imposing a sentence on the defendant. In this study, the proposed method to examine and analyse the strength of the items or evidence were obtained through the expert witnesses and field witnesses. Here, we analyse empirical juridical legal studies are examines the applicable legal provisions and a society reality condition. In this study, the processing data was used qualitative methods with draws conclusions using legal logic. The result shows the judges' considerations and decisions are sometimes different from the demands of the public prosecutor. In addition, the evidence and considerations used by the panel of judges also differ from the evidence received from expert witnesses, field witnesses, letters and instructions from investigators. However, the judges have a strength evidence to determine authority by obtain relationship.